Angioedema in pediatric liver transplant recipients under tacrolimus immunosuppression - Panayotis Lykavieris; Élisabeth Frauger; Dalila Habès; Olivier Bernard; Dominique Debray (2003)
Background. The authors report on their experience with food-induced angioedema in tacrolimus-immunosuppressed pediatric liver recipients. Methods. Among 121 children treated with tacrolimus after liver transplantation, those who presented with angioedema are reported. Results. Twelve children (10%) experienced angioedema related to food allergy while on tacrolimus. Mean ages at transplantation and angioedema were 1.3 years and 3.75 years, respectively. Angioedema occurred within a mean of 28 months from onset of tacrolimus. Eleven children experienced two or more angioedema attacks without consequences. One child presented with anaphylactic shock that caused postischemic cerebral damage. Besides eviction of food allergens, eight children were switched from tacrolimus to cyclosporine, whereas tacrolimus dosage was decreased in four. Reintroduction of food allergens was successfully performed only in those who were switched to cyclosporine. Conclusion. A causal relationship between tacrolimus and the occurrence of food-induced angioedema is suggested. The switch from tacrolimus to cyclosporine should be considered.